“I have a gun and I know how to use it”: A phenomenology of handgun ownership by evangelical Christians - Rosell, Tarris D. (Review and expositor, 2020)
American gun culture pervades American evangelicalism. Field research of this phenomenon utilizes phenomenological methods, involving online and onsite visits to Frontier Justice, a Kansas City-based gun store and boutique with evangelical Christian owners. Additional research entails concealed-carry gun training and interviews and email correspondence with Christian handgun owners, including the pastor of a church with armed security. Research culminates with the purchase of a used handgun for specified purposes. Theological ethics reflection controversially correlates the phenomenon of dutiful or fanatical evangelical gun ownership with fear, idolatry, and narcissism.